DETERMINATION OF HEAVY METAL-INDUCED DNA DAMAGE IN PISUM SATIVUM L. AT THE MOLECULAR AND POPULATION LEVEL - Yonca Surgun-Acar (Journal of Animal and Plant Sciences, 2018)
-1 In the current study, the effects of heavy metals on pea (Pisum sativum L.), which were exposed to 150 mg L and 300 -1 mg L Cd, Pb and Cu treatments for 12 days, were investigated by using population parameters and Random Amplified Polymorphic DNA (RAPD) assay in the roots and leaves. In RAPD assay, 17 RAPD primers generated polymorphic band profiles, and a total of 110 bands were produced in the leaves and roots of the control seedlings. Changes were detected in the RAPD patterns of the roots and leaves of the pea plants that subjected to heavy metal treatment in terms of band intensities, appearance of new bands and disappearance of bands. The changes in the RAPD patterns were found to be more in roots when compared leaves. The results of germination, shoot and primary root length showed a correlation with the genomic template stability ( GTS) values. Determination of the DNA damage by using the RAPD assay together with different biomarkers may be a practical eco-genotoxicological tool in the biomonitoring of chemical contaminants. causes oxidative stress when found in high concentrations
Keywords: Pea (Pisum sativum L.); heavy metal; genotoxicity; growth parameters.